Bengali Upasarga: A morphological analysis - Khairunnahar, Khondokar (Dhaka University Journal of Linguistics, 2009)
In Bengali an upasarga- a special kind of prefx- is a vibrant element which is determined as bound morpheme in a morphological consideration. If words are analyzed structurally, the result is outnumbered words, which are mainly constructed by such a prefix. More specifically, most of the terms in Bengali are created with the help of these prefixes. Thus, the main goal of this paper is to provide a structural interpretation of such bound morphemes enriching the words in Bengali. Key words: prefix, bound morpheme, class changing, class maintaining, morphology DOI: 10.3329/dujl.v1i2.3722 The Dhaka University Journal of Linguistics: Vol.1 No.2 August, 2008 Page: 157-168